Determination of erodibility under different land uses in the vicinity of Nirjuli, Arunachal Pradesh - DABRAL, P. P.; CHOUDHURY, ASHISH; BARMAN, MRIDUSMITA; PANDEY, P. K. (Journal of Soil and Water Conservation, 2020)
In the vicinity of Nirjuli (study area), five types of land uses are prominent and this study is aimed to find the erosive nature of the study area. Soil samples were collected from two depths i.e. 0-15, 15-30 cm from 5 land uses in the vicinity of Nirjuli. Various erodibility indices, i.e. erosion ratio, dispersion ratio, clay/moisture equivalent ratio, moisture equivalent were worked out. Correlation and regression equations were developed among erodibility indices. Mechanical composition of the soils of the experimental site reveals that in all land uses, soils were found to be coarser in texture. Results suggested that all soils (top surface and sub-surface) were found to be highly erodible as the value of dispersion and erosion ratio was more than 15 and 10, respectively in all land uses. The correlation between erosion ratio and dispersion ratio was found to be highly significant and positive. The dispersion ratio which is much easier to determine and therefore is recommended for determining the erodibility behaviour of the soils in the study area.